The Determinants of Tax Revenue in the Context of International Transactions in the Latin America and Caribbean (LAC) Regions 2002-2019 - Hendiva Tri Nugraha; Suparna Wijaya (Ilomata International Journal of Tax and Accounting, 2023)
Tax revenue is one of the backbones of economy in almost every country in the world. There are several determinants that influence the amount of tax revenue in one country, one of which is international transaction activities. Such activities can partly be presented by three variables; Foreign Direct Investment (FDI), Trade Openness (TO), and External Debt. This study aims to acknowledge the effects of international transaction experienced by a country regarding its tax revenue. External Debt is used as a moderating variable to the effects of FDI and TO on tax revenue. The data source was taken from the World Bank within the period of 2002-2019 in 19 countries around LAC regions. The study implements an associative quantitative method with PCSE regression. The result showed that FDI affects tax revenue negatively, whereas trade openness and external debt affect tax revenue positively. External debt as a moderating variable strengthens the effect of FDI and weakens the effects of trade openness to tax revenue. Further research is expected to include all the LAC countries, add more variables relevant to the international transactions, and renew the research period.